Efforts to improve by provision of infrastructure services and extracuricular implementation learning achievement - Aminah Aminah; Edi Harapan; Achmad Wahidy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The main objective of this research is to define and explain, through the provision of facilities and extracurricular implementation, the enhancement of student learning achievement. The data collection tool is observation, questionnaires and documentation. Quantitative research is the type of research performed in this study. The sampling technique in this study was purposive random sampling, namely all 125 students of MTs N Sekecamtan Sekayu. The approach used is the methodology of descriptive analysis and multiple linear regression. Using SPSS version 23 for windows, the data was analyzed descriptively.From the results of the analysis test shows that; The simultaneous influence of the provision of infrastructure and implementation of extracurricular activities on improving learning achievement. There is a substantial rise in the provision of learning achievement facilities. The implementation of extracurricular activities on student achievement is dramatically growing